2018
DOI: 10.1016/j.rser.2018.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the main opportunities of integrated biorefining from agro-bioenergy co/by-products and agroindustrial residues into high-value added products associated to some emerging markets: A review

Abstract: Market implementation of integrated biorefinery requires reliable and advanced processing units combined with ecofriendly and economically profitable production chains. Future developments of the biorefinery systems should include either crop cultivation with selected genotypes that maximize full chain performance either the use of marketable agricultural residual biomass and agro-waste. The aim of the present work was to review the main biorefining opportunities of disposable agricultural residues, agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(77 citation statements)
references
References 88 publications
(84 reference statements)
0
67
0
4
Order By: Relevance
“…If Brassicaceaes are grown as a rotation crop, farmers lose time for their cash crops. Thus, and also due to the fact that seed meal or oil-less seed cakes contain high amounts of glucosinolates, the use of these by-products of the biofuel production can enable the provisioning of the required biomass [94,95].…”
Section: Biofumigationmentioning
confidence: 99%
“…If Brassicaceaes are grown as a rotation crop, farmers lose time for their cash crops. Thus, and also due to the fact that seed meal or oil-less seed cakes contain high amounts of glucosinolates, the use of these by-products of the biofuel production can enable the provisioning of the required biomass [94,95].…”
Section: Biofumigationmentioning
confidence: 99%
“…The use of artichoke waste for the recovery of phenolic compounds and bioenergy production has been suggested by Zuorro et al (2016), while Petropoulos et al (2017Petropoulos et al ( , 2018a have reported the bioactive compounds profile of cardoon plant parts for potential use in the pharmaceutical industry. While the byproducts of both cotton and cardoon processing are considered bulky biowaste (De Corato et al, 2018), the increasing demand of nonsynthetic, renewable, and locally available growing media for soilless-grown horticultural crops may open new perspectives for the use of these materials as substitute of peat-based growing media (Di Gioia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing sludge reduction leads to decomposition of organic matter and increased biogas generation. Volatile solids reduction efficiency is important because biogas production leads to an increase in methane gas generation, although there are some differences depending on the properties of the substrate [23,31]. In this experiment, the COD reduction value was 30.4%, 68.5%, 83.6%, and 46.66% for SF1, SF2, SF3, and SF4, respectively (Fig.…”
Section: Sludge Reduction In Anaerobic Co-digestionmentioning
confidence: 74%
“…The methane content of a typical anaerobic digestion gas ranges from 55% to 70% [15]. According to previous studies, higher methane content (over 70%) results in higher quality biogas [22,31]. Production of biogas using FFB is significant because it contains more methane than other feed stocks, offering the possibility of biogas production using FFB.…”
Section: Characterization Of Produced Biogasmentioning
confidence: 99%
See 1 more Smart Citation